2012
DOI: 10.1177/1356766712449369
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted Webnography

Abstract: Through social media applications, consumers are increasingly participating in information processes. When booking a journey, consumer opinions exchanged via modern media shape the reputation of enterprises like travel agencies and thus have a major impact on the decision to book a journey. Online market research is regarded as a crucial tool to steer these online discourses, with the emphasis on quantitative analyses. However, looking at the Web as a social forum can provide additional insights. Taking user-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In this new intercommunicating world, a new concept appears to define customers' opinions: the firm's reputation [25,26]. When shared over the Internet, this reputation is called the online reputation [27][28][29], and it has a direct influence on the purchasing behavior of customers in industries where communication through the Internet is essential in developing the main business [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In this new intercommunicating world, a new concept appears to define customers' opinions: the firm's reputation [25,26]. When shared over the Internet, this reputation is called the online reputation [27][28][29], and it has a direct influence on the purchasing behavior of customers in industries where communication through the Internet is essential in developing the main business [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In [11], Horster, E., & Gottschalk, C. introduced a novel methodology called computer-assisted webnography to enhance online reputation management in the tourism industry. Their task involved developing a systematic approach to analyze and interpret digital traces of consumer-generated content, such as online reviews, social media posts, and forum discussions, to gain insights into destination perceptions, traveler behaviors, and reputation dynamics.…”
Section: Related Workmentioning
confidence: 99%
“…Schroeder et al (2013) examined how social media affects tourists' risk perceptions. Hoster and Gottschalk (2012) studied how to use social media for corporate image restoration after a disaster. Sano and Sano (2019) found that consumer-to-consumer communication can result in higher security perception and travel intention than business-to-consumer communication.…”
Section: Theoretical Backgroundmentioning
confidence: 99%